Personality and earnings - Kaye K. W. Lee (Levy Economics Institute of Bard College, 2006)
This paper studies personality as a potential explanation for wage differentials between apparently similar workers. This follows initial studies by Jencks (1979) that suggest that certain personality traits, such as industriousness and leadership, have an impact on earnings. The paper aims to provide a theoretical framework within which these effects may be analyzed. The study begins by outlining four issues as a backdrop to the model: rationality, the industry, firms, and workers. A crucial factor to the model is the meme-a mental gene that affects personality. Taking these four factors into consideration, the Contested Exchange model from Bowles and Gintis (1990) is used. Then, it is adapted to study memetic effects on the wage rate. This is followed by an analysis of how memes may affect personality and thus earnings. The issues that require further study and resolution are 1) which traits create wage ifferentials, and 2) two-way causality: does personality affect the wage, or does a wage premium become an incentive for a person to adopt new memes?
Keywords: 330